2018
DOI: 10.1371/journal.pone.0206506
|View full text |Cite
|
Sign up to set email alerts
|

Radiolysis via radioactivity is not responsible for rapid methane oxidation in subterranean air

Abstract: Atmospheric methane is rapidly lost when it enters humid subterranean critical and vadose zones (e.g., air in soils and caves). Because methane is a source of carbon and energy, it can be consumed by methanotrophic methane-oxidizing bacteria. As an additional subterranean sink, it has been hypothesized that methane is oxidized by natural radioactivity-induced radiolysis that produces energetic ions and radicals, which then trigger abiotic oxidation and consumption of methane within a few hours. Using controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In fact, one of the important •OH sources in cave air may be from radioactive 222 Rn decay [34]. However, further research verified that the mechanism of CH 4 consumption was seasonally changing and methane-oxidizing bacteria were primarily responsible for the widespread observations of CH 4 depletion in subterranean environments, discarding any evidence of radiolysis contribution [37][38][39].…”
Section: The Control Of Greenhouse Gas Fluxes By Cave Microorganismsmentioning
confidence: 97%
See 1 more Smart Citation
“…In fact, one of the important •OH sources in cave air may be from radioactive 222 Rn decay [34]. However, further research verified that the mechanism of CH 4 consumption was seasonally changing and methane-oxidizing bacteria were primarily responsible for the widespread observations of CH 4 depletion in subterranean environments, discarding any evidence of radiolysis contribution [37][38][39].…”
Section: The Control Of Greenhouse Gas Fluxes By Cave Microorganismsmentioning
confidence: 97%
“…Schimmelmann et al [37] tested, in controlled laboratory experiments, whether radiolysis could rapidly oxidize CH 4 in sealed air with different relative humidity and elevated levels of radiation from Rn isotopes. No evidence of CH 4 oxidation by radiolysis was found.…”
Section: The Control Of Greenhouse Gas Fluxes By Cave Microorganismsmentioning
confidence: 99%
“…The authors followed up with practical experiments which demonstrated that rates of microbial methane oxidation in caves are in fact high and could reduce concentrations of gaseous methane (Lennon et al, 2017 ). In a later paper, Lennon and colleagues collaborated with two authors of the Fernandez‐Cortes et al ( 2015 ) paper to experimentally test whether radiation can oxidise methane at rates sufficient to support the original suggestion by Fernandez‐Cortes et al (Schimmelmann et al, 2018 ). The Lennon et al ( 2017 ) study was useful for understanding the contributions of microorganisms to the overlooked sink of greenhouse gases that may be important for local and regional climate‐change modelling.…”
Section: When Theory Is the Most‐appropriate Route To Scientific Noveltymentioning
confidence: 99%
“…A computer fan drew air from the space between the mud wall and a wooden board through a central hole in the board into a perforated polyethylene enclosure that contained the SARAD R Thoron Scout. Although the Thoron Scout is a passive thoron detection device without an internal pump, the active air flow from an external fan makes its thoron data compatible with those from the SARAD R RTM 2200 with an internal pump (Schimmelmann et al, 2018). Hourly average 220 Rn isotope concentrations in room air were automatically logged by the Thoron Scout from November 8, 2017 until January 14, 2018, with a small hiatus in early January.…”
Section: Rn Exhalation In a Mud Housementioning
confidence: 99%